Controle sanitário e ambiental de um projeto de reúso em um complexo de prédios corporativos - Santos, Jobson Luiz Prazeres dos (2011)
The study that resulted in this dissertation was developed at OU RNCE PETROBRAS, in Natal, which implemented a project of rational use and reuse of water, including use of wastewater from a Sewage Treatment Plant (STP) already in place, diluted with water from own wells for irrigation of green area of the building complex corporate enterprise. Establish a methodology that can serve as guidelines for future projects controlled reuse of water like this was the objective of this research. Been proposed, implemented and evaluated three instruments of sanitary and environmental control: 1) adaptation of sewage treatment plant and quality control of the treated effluent 2) analysis of soil-nutrient interaction in the irrigated area, 3) knowledge of the local hydrogeology, especially with regard to the direction of flow of the aquifer and location of collection wells of Companhia de Águas e Esgotos do Rio Grande do Norte (CAERN) situated in the surroundings. These instruments have proven sufficient and appropriate to ensure the levels of sanitary and environmental control proposed and studied, which were: a) control of water quality off the STP and the output of the irrigation reservoir, b) control of water quality sub surface soil and assessment of progress on soil composition, c) assessment of water quality in the aquifer. For this, we must: 1) establishing the monitoring plan of the STP and its effluent quality sampling points and defining the parameters of analysis, improve the functioning of that identifying the adequacy of flow and screening as the main factors of operational control, and increase the efficiency of the station to a relatively low cost, using additional filters, 2) propose, implement and adapt simple collectors to assess the quality of water percolating into the soil of the irrigated area, 3) determine the direction of groundwater flow in the area study and select the wells for monitoring of the aquifer.